2003
DOI: 10.1038/sj.gt.3301911
|View full text |Cite
|
Sign up to set email alerts
|

Function of a genetically modified human liver cell line that stores, processes and secretes insulin

Abstract: An alternative approach to the treatment of type I diabetes is the use of genetically altered neoplastic liver cells to synthesize, store and secrete insulin. To try and achieve this goal we modified a human liver cell line, HUH7, by transfecting it with human insulin cDNA under the control of the cytomegalovirus promoter. The HUH7-ins cells created were able to synthesize insulin in a similar manner to that which occurs in pancreatic b cells. They secreted insulin in a regulated manner in response to glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 44 publications
7
74
0
1
Order By: Relevance
“…The 140-fold lower insulin content of both CGA and NR cells, as compared to GR cells (Fig. 8) 10 and is consistent with this conclusion. The comparatively low proinsulin levels in medium bathing CGA and NR cells (proinsulin:insulin ratio 0.54 and 0.73% respectively) are consistent with the effect of the converting enzymes PC1 and PC2 found in the cytoplasm.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The 140-fold lower insulin content of both CGA and NR cells, as compared to GR cells (Fig. 8) 10 and is consistent with this conclusion. The comparatively low proinsulin levels in medium bathing CGA and NR cells (proinsulin:insulin ratio 0.54 and 0.73% respectively) are consistent with the effect of the converting enzymes PC1 and PC2 found in the cytoplasm.…”
Section: Resultssupporting
confidence: 86%
“…According to current literature the combination of CgB and CgA in a cell should lead to the formation of granulelike structures in the cytoplasm. 1,2 The absence of such structures in HUH7 cells, 10 but their presence in HUH7-ins cells, cannot be explained by previous knowledge of SGB.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Also as long as the cells remain in the capsule, agents such as viruses might not be released (although there are reports that at least retroviruses can be released from encapsulated cells [6]. Other sources of cells include human stem cells that can be differentiated into insulin producing cells such as mesenchymal stem cells [7] as well as cells that are genetically modified to produce insulin [8].There has been some concern that certain earlier clinical • Ability to reproducibly source, produce and characterize the starting material.…”
Section: Source Of Cellsmentioning
confidence: 99%
“…An emerging approach that holds promise is the transdifferentiation of hepatocytes into insulin-secreting cells that are capable of storing and secreting insulin in a very similar way like b-cells. Gene transfer of the transcription factors pancreatic and duodenal homeobox gene 1 (PDX1) and NeuroD into hepatocytes or a modified neoplastic human liver cell line (HUH7) has been demonstrated to ameliorate STZ-induced hyperglycemia in mice (79,106). Recently, Kojima et al showed that hepatocytes transfected with NeuroD and betacellulin, a b-cell growth factor, is able to drive the formation of insulin-producing cells and normalizes blood glucose levels in STZ-induced diabetic mice (107).…”
Section: Regulation Of Insulin Secretion In Transduced Hepatocytementioning
confidence: 99%